Preterm Birth’s Effects on Attachment - Elif Yerlikaya Oral; Gül Karaçetin (Cam & Sakura Medical Journal, 2024)
The attachment established between the caregiver and the infant is a fundamental factor affecting mental health, starting from the prenatal period and developing during infancy. Prematurity is among the factors that influence the quality of attachment, making it difficult for healthy parent-child relationships to be established. Premature infants treated in intensive care units must separate emotionally and physically from their caregivers, putting them and their parents at risk of mental health problems and interrupting the attachment process. With the increase in premature birth rates, studies have investigated the relationship between attachment quality and premature birth, concluding that premature birth negatively affects secure attachment and that attachment quality decreases as gestational age decreases and neonatal intensive care time increases. Protective interventions and multidisciplinary approaches are recommended to reduce this negative effect, and long-term studies are needed to better understand the relationship.